2021
DOI: 10.30574/wjaets.2021.2.2.0044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate the thermal performance of the dryer using a perforated wall furnace-heat exchanger for drying

Abstract: The use of heat exchangers for the process of energy conversion from rice husks to thermal as an alternative to replacing sun drying. Drying with rice husk energy and heat exchanger does not depend on the weather. To determine the effectiveness of this dryer, a thermal evaluation was carried out on the heat exchanger and drying chamber with a sample of 4 kg of shelled corn. The test results showed an increase in the drying temperature of 112.31%. The increase occurred from an average environmental temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the past, many researchers tried to design, develop, and evaluate the performance of a mixed-flow grain dryer that uses different energy sources mostly electric heaters. Scholars design and develop different grain dryers using rice husk as an energy source for hot air generation and these researches showed that rice husk is an alternative solution to other expensive energy sources [ [28] , [29] , [30] , [31] , [32] , [33] ]. develop and evaluated the performance of rice husk fueled shelf type dryers for corn, jackfruit, cassava, and rice drying.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, many researchers tried to design, develop, and evaluate the performance of a mixed-flow grain dryer that uses different energy sources mostly electric heaters. Scholars design and develop different grain dryers using rice husk as an energy source for hot air generation and these researches showed that rice husk is an alternative solution to other expensive energy sources [ [28] , [29] , [30] , [31] , [32] , [33] ]. develop and evaluated the performance of rice husk fueled shelf type dryers for corn, jackfruit, cassava, and rice drying.…”
Section: Introductionmentioning
confidence: 99%